Pemberdayaan Perempuan Pantai Beting dalam Pengolahan Dodol Mangrove - Sri Hapsari Wijayanti; Francisca Hermawan; Yussi Ramawati (Universitas Serang Raya, 2018)
Mangrove was found in Pantai Beting, Muaragembong sub-district, Bekasi, West Java. However, not many people there maximize the potential of natural mangrove to be processed into a product of economic value. By relying on the abundant potential of mangrove pidada, women in Pantai Beting need to be empowered. Therefore, the purpose of this activity is to provide (1) making of pidada’s dodol production, packaging, and marketing of its business; (2) post-training evaluation and monitoring. The subject of this activity is 22 women who live in Pulau Beting. The method used is the practise of making dodol by local facilitator. In addition, we used lecture, discussion, and demonstration methods are used to provide packaging and marketing training. Evaluation and monitoring are delivered by interview and FGD methods by focusing on the marketing mix, ie product, price, place, and promotion. This activity produces different lunkhead products than before. Differences include the level of cleanliness, dodol shape, and its packaging. The price also has been adjusted. The place of marketing is still done by the producer or through the acquaintance of market. Promotion is not just word of mouth (WOM), but has been up to marketing online though intermediaries by someone.